1994
DOI: 10.1136/jnnp.57.8.903
|View full text |Cite
|
Sign up to set email alerts
|

The Sydney Multicentre Study of Parkinson's disease: a randomised, prospective five year study comparing low dose bromocriptine with low dose levodopa-carbidopa.

Abstract: 149 previously untreated patients with Parkinson's disease were recruited over a three year period and randomly allocated to either low dose levodopa-carbidopa

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
133
0
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(141 citation statements)
references
References 25 publications
6
133
0
2
Order By: Relevance
“…Likewise, the moderate and unchanged level of the lisuride dosage (average 1 mg/day) shows that, by tapering in by 0.1 mg graduations per week and with a good understanding of the expected undesirable effects, the investigators rapidly found what appeared to them as the optimal dosage. The observed undesirable effects (psychiatric effects including sleep disorders, digestive disorders such as nausea and vomiting at treatment onset) were in agreement with published data concerning dopaminergic agonists [22, 23, 24, 25, 26, 27, 28]. …”
Section: Discussionsupporting
confidence: 80%
“…Likewise, the moderate and unchanged level of the lisuride dosage (average 1 mg/day) shows that, by tapering in by 0.1 mg graduations per week and with a good understanding of the expected undesirable effects, the investigators rapidly found what appeared to them as the optimal dosage. The observed undesirable effects (psychiatric effects including sleep disorders, digestive disorders such as nausea and vomiting at treatment onset) were in agreement with published data concerning dopaminergic agonists [22, 23, 24, 25, 26, 27, 28]. …”
Section: Discussionsupporting
confidence: 80%
“…Clinical studies randomly assigning patients to initial treatment with a dopamine agonist or levodopa have shown a lower risk for dyskinesias in the agonist-treated groups (agonists studied have included pramipexole [22, 61], ropinirole [23, 62], bromocriptine [63, 64], pergolide [65], and cabergoline [21]). Retrospective analyses have demonstrated that once levodopa is added, the rate of development of dyskinesias is the same regardless of whether or not the patient was already taking a dopamine agonist [62, 66].…”
Section: Pharmacologic Strategies To Directly Address the Incidence Omentioning
confidence: 99%
“…However, during long-term use of L-dopa, many patients with Parkinson's disease develop motor response fluctuations that, in many cases, force treatment discontinuation (eg, wearing off, on-off fluctuations, night-time deterioration, early morning worsening, and dyskinesias). 9,10 These side effects have been linked to fluctuations of striatal dopamine levels during intermittent L-dopa therapy, and some success in reducing them has been obtained with the use of slow-release L-dopa formulations. 11 The currently available pharmacologic and nonpharmacologic treatments are capable of offering only symptomatic relief for patients.…”
Section: Introductionmentioning
confidence: 99%